Rising trends in the use of frozen dog sperm: a retrospective study in Belgium and the Netherlands - Domain, Guillaume; Kappen, Maarten; Van Mil, Amber; De Beijer, Ilse; Van Puyvelde, Matthieu; Van Leeuwenberg, Robby; Spanoghe, Lotte; Posastiuc, Florin; Van Soom, Ann (Frontiers in Veterinary Science, 2024)
IntroductionSperm cryopreservation is a valuable technique for storing valuable canine genetics. However, little is known concerning the fate of frozen sperm stored in a sperm bank. This study aimed to characterize dogs presented for sperm cryopreservation and describe the use and popularity of frozen sperm in the Netherlands and Belgium over recent years.MethodsMedical records from dogs presented for sperm cryopreservation between January 1, 2014 and December 31, 2022 at two different freezing centers were reviewed retrospectively. Imported frozen sperm was excluded due to lack of usage information. Each sperm cryopreservation was considered a single event, and data were collected separately for each cryopreserved sample.ResultsA total of 3,090 ejaculates from 1,040 males of 157 different breeds were included and investigated using exploratory data analysis. The findings showed a steady rise in the popularity of sperm cryopreservation, with annual growth rates ranging from 8.4 to 41.9%. The majority of dogs (88.5%) were between 1 and 9 years old at the time of sperm cryopreservation, with nearly one-third aged 2–4 years. Most dogs were collected for sperm cryopreservation once (62.8%) or twice (21.6%). Sperm banks were used for both short- and long-term storage needs, and 6.83% of ejaculates were eventually discarded. The primary use of froze sperm was for international shipment, while 21.8% was used locally for artificial insemination. Depending on the year of cryopreservation, between 44.1 and 79.6% of frozen ejaculates remained unused or only partially used at the time of data collection.DiscussionThe results of this study provides the first comprehensive analysis of the use and popularity of frozen sperm among dog breeders in Belgium and the Netherlands and suggest a change in breeding practices in recent years. The percentage of breeders resorting to sperm cryopreservation and the extent of frozen sperm use in current breeding strategies remain to be defined in future studies.